2004
DOI: 10.1111/j.0105-2896.2004.00132.x
|View full text |Cite
|
Sign up to set email alerts
|

The major histocompatibility complex origin

Abstract: The present review focuses on the history of genes involved in the major histocompatibility complex (MHC), with a special emphasis on class I function in peptide presentation. The MHC class II story is covered in less detail, as it does not have a major impact on the general understanding of the MHC evolution. We first redefine the MHC as the definition evolved over time. We then use phylogenetic analysis to investigate the history of genes involved in the MHC class I process. As not all the genes involved in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
49
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 71 publications
3
49
0
Order By: Relevance
“…Recent studies of amphioxus and ascidian genome revealed that just a proto-MHC region existed in these protochordate (12,44). In our amphioxus libraries, we also found the homologues of BAT5, allograft inflammatory factor 1 (AIF1), RING2 (KE6), KE2 (Fig.…”
Section: Homologues Of Ag Peptide Processing and Presentation Genes Asupporting
confidence: 52%
See 1 more Smart Citation
“…Recent studies of amphioxus and ascidian genome revealed that just a proto-MHC region existed in these protochordate (12,44). In our amphioxus libraries, we also found the homologues of BAT5, allograft inflammatory factor 1 (AIF1), RING2 (KE6), KE2 (Fig.…”
Section: Homologues Of Ag Peptide Processing and Presentation Genes Asupporting
confidence: 52%
“…The Ag presentation system in AIS involved many proteases and chaperones, and Danchin et al (44) demonstrated that many of them gained their specific function in Ag processing and presentation through various levels of co-option. Many homologues of proteasomes and chaperones were found in our database.…”
Section: Homologues Of Ag Peptide Processing and Presentation Genes Amentioning
confidence: 99%
“…The MHC was genetically defined more precisely by Snell (1948), who first used the term. It has been recognized as a large multigene family present in all jawed vertebrates (Danchin et al, 2004;Kelley et al, 2005). During the last two decades, MHC genes, especially class I and MHC Class I Exon 4 in the Multiocellated Racerunners (Eremias multiocellata): Polymorphism, Duplication and Selection Xiuyun YUAN 1,2 , Xiaomao ZENG 1 and Xianguang GUO 1* are evolving under balancing selection are distinct from neutral loci in that they show high levels of heterozygosity and a large number of alleles at similar frequencies (Maruyama and Nei, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of CD1 in birds also provides some fascinating insights into the possible features of the primordial MHC, which is thought to have arisen with the very earliest vertebrates or protochordates (13). Based on experimental data and the publicly available draft sequence of the G. gallus genome, the chCD1-1 and chCD1-2 genes map to the MHC locus, unlike what has so far been found for mammalian CD1 genes.…”
mentioning
confidence: 99%
“…The separation of CD1 and MHC loci in mammals is presumed to have occurred as a result of duplication and relocation of the ancestral MHC locus to create one or more paralogous loci on different chromosomes. Indeed, evidence exists for at least three such MHC paralogous loci in the human genome, one of which is the CD1 locus on chromosome 1 (13,14). In this evolutionary scheme, subsequent shaping of the genome after these duplication events led to deletion of the CD1 genes from the modern MHC locus in mammals and deletion of the MHC class I and II genes or their precursors from the CD1 locus, thus creating two distinct loci with related genes.…”
mentioning
confidence: 99%